Cellular pharmacology studies of anticancer agents: recommendations from the EORTC-PAMM group - Perego, Paola; Hempel, Georg; Linder, Stig; Bradshaw, Tracey D.; Larsen, Annette K.; Peters, Godefridus J.; Phillips, Roger M. (Springer, 2017)
An increasing number of manuscripts focus on the in vitro evaluation of established and novel anti-tumour agents in experimental models. Whilst the design of such in vitro assays is inherently flexible, some of these studies lack the minimum information necessary to critically evaluate their relevance or have been carried out under unsuitable conditions. The use of appropriate and robust methods and experimental design has important implications for generating results that are reliable, relevant, and reproducible. The Pharmacology and Molecular Mechanisms (PAMM) group of the European Organization for Research and Treatment of Cancer (EORTC) is the largest group of academic scientists working on drug development and bundle decades of expertise in this field. This position paper addresses all researchers with an interest in the preclinical and cellular pharmacology of anti-tumour agents and aims at generating basic recommendations for the correct use of compounds to be tested for anti-tumour activity using a range of preclinical cellular models of cancer.